Identifying Potential Exosome-Derived mRNA Biomarkers for Diagnosis and Prediction of Breast Cancer Using Machine-Learning Approaches - Chenhao Li; Chunyan Wei; Qijia Tian; Dechao Bu; Yang Ge; Mingdi Zhang; Xiaolin Hu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Geopolymer Stabilization of Dried Dredged Soil Using Slag and Fly Ash for Pile Applications - Shuangxi Feng; Tianhao Bu; Huayang Lei; Jiankai Li; Xinyue Wang; Yunyang Ge (Geotechnical and Geological Engineering, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

TS-TCN: a deep learning model for ultra-short-term outdoor air temperature forecasting in complex terrain with small sample size - Shun Wu; Jie Shao; Ge Li; Xiushu Pu; YuanChang Dong; Tao Du; Jinrong Kang; Bu Zhao (Energy and Buildings, 2026)

The role of amino acid signaling in pathogenesis of chronic kidney disease - Siya Yan; Xiangqi Zhang; Ruizhen Bu; Ge Li; Yang Wang; Meifang Cheng; Qian Chen; Yuzheng Wu; Yi Zhang; Dan Wang; Tao Wang (Molecular and Cellular Biochemistry, 2025)

Paleoecology and paleoclimate across the Early Cretaceous Xing'anling Group: New palynological and radiometric data from the Hailar Basin (NE China) - Yan Zhang; Iván R. Barreiro; Chuan-biao Wan; Yue-wu Sun; Wen-chun Ge; Yun-fei Xue; Ti Li; Xin Zhang; Chun-yang Bu; Hao Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

STC2 regulates the proliferation, migration and glycolysis of glioma cells through modulating ITGB2 - Zefeng Wei; Dengfeng Ge; Jie Bu; Xuenan Wang; Tao Zhong; Xiaoxiao Gongye; Bin Zhang; Feng Yan; Chunyan He; Runhan Guo; Jiayi Li; Zhenzhen Jin (Metabolic Brain Disease, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Deciphering the role of particulate organic matter in soil nitrogen transformation in rice–rapeseed and rice–wheat rotation systems - Rongyan Bu; Shang Han; Wenlong Cheng; Yue Wu; Shan Tang; Min Li; Hui Wang; Zibing Ge; Ji Wu (Applied Soil Ecology, 2024)

Contrasting effects of nitrogen and phosphorus additions on fine root production and morphological traits of different plant functional types in an ombrotrophic peatland - Leming Ge; Chen Chen; Tong Li; Zhao-Jun Bu; Meng Wang (Plant and Soil, 2023)

Analysis of microbial community and its correlation with flavor compounds during Congee fermentation - Yang Yang; You Na Wu; Li Ge Er Ce; Xi Ge Bu Ren Ge; Quan Shuang; Feng Mei Zhang (Food Bioscience, 2023)

Design strategies of perovskite nanofibers electrocatalysts for water splitting: A mini review - Yaobin Wang; Yan Jiang; Yunxia Zhao; Xinlei Ge; Qian Lu; Ting Zhang; Dongsheng Xie; Meng Li; Yunfei Bu (Chemical Engineering Journal, 2023)

Research on system of flood disaster control and reduction supported by gis in medium and small basins - You-peng Xu; Jin-kang Du; Li-feng Zhang; Xiao-ping Ge; Bu-zhu Peng (Chinese Geographical Science, 2002)